Фенотипічна мінливість структури епідермісу та кремнієві включення у листках Quercus robur у парку “Феофанія” - Nedukha, Olena; Zolotareva, Olena; Netsvetov, Maksym (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2023)
The micromorphology of the leaf epidermis, localization, and silicon content in the epidermal cells of Quercus robur leaves growing in the shade and under direct sunlight in the Feofaniya Park (Kyiv, Ukraine) were studied using scanning electron microscopy and laser confocal microscopy. Silicon inclusions were found in the anticlinal and periclinal walls of adaxial epidermal cells, trichomes, guard cells of stomata, and walls of regular epidermal cells on the abaxial leaf surface, the amount of which varied according to the conditions of growth. Natural shading and the intensity of solar irradiation were found affecting the size of leaf blades, the ultrastructure of the leaf epidermis, and changes in the silicon content of oak leaves. Studies have shown that the anticlinal walls of the adaxial epidermis and the trichomes and stomata of the abaxial epidermis of leaves are the main silicon accumulators. The findings suggest that changes in leaf microstructure and silicon content contribute to maintaining optimal water balance in plants and can be regarded as signs of phenotypic plasticity in plants and an adaptive marker depending on the sunlight conditions of oak growth.